Qualitative Methodologies in Organization Studies Volume I: Theories and New Approaches (Springer International Publishing, 2018)
'This current and timely collection brings together an impressive group of contributors, providing us with a comprehensive and detailed view of qualitative methods as practiced today; of benefit to any qualitative researcher in business and management. Highly recommended.' -Yochanan Altman, Professor of International HRM, Middlesex University, UK 'This book is a carefully curated cornucopia of insights for both early career and experienced qualitative researchers seeking to understand the complex social and organizational world we live in.' -Rob Wilson, Chair of Information Systems Management and Director of the Knowledge Innovation Technology Enterprise Research Centre, Newcastle University, UK 'The editors provide us with an inspiring reservoir of intellectual knowledge on how, when and why we apply qualitative methods in organizational studies. The book is highly recommended for researchers interested in organizations - or other social settings - to dive into this reservoir of approaches and theories.' -Ann Westenholz, Professor Emeritus, Copenhagen Business School, Denmark This book brings together key theories behind qualitative research, whilst drawing attention to novel, cutting-edge approaches to data gathering, such as visual anthropology and storytelling. Offering a comprehensive guide to qualitative analysis, this book goes further than examining research methods to open a discussion on the roles of reflexivity, imagination, emotions and ethics in qualitative research, Covering topics such as reflective analysis, sociological paradigms, action research and organizational ethnography, this book is ideal reading for those who wish to address the gap between undergraduate and postgraduate research-based edited books and encompasses a wide array of methods. Those exploring organization studies will find this two-volume collection extremely valuable as it contains robust contributions from highly-skilled authors who are actively researching in this field.